Implementation of Stunting Prevention Policies in Gampong Alue Pineung Timue: Synergy of Community Values and Public Policy - agustinar, Agustinar; Nurjannah; Eliza, Zulfa; Safwandi; Asnita, Dessy; Zuliani, Rafiza; Sumarni, Mutia (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2024)
Abstract The issue of stunting among children in Gampong Alue Pineung Timue is caused by inadequate nutrition intake over a prolonged period. This problem is of serious concern due to its impact on children's growth and development. The aim of this paper is to implement a stunting prevention policy with a public value approach as its foundation. The methods include workshops and educational mentoring for the community, particularly for stunting cadres in Gampong Alue Pineung Timue. These activities aim to enhance community understanding of factors contributing to stunting, such as political economy, health, sanitation, and environment. The results of this policy implementation demonstrate strong commitment from the Government of Gampong Alue Pineung Timue through Presidential Regulation No. 72 of 2021, encompassing various nutrition and health interventions. In conclusion, addressing stunting requires collective commitment and sustainable policy implementation from multiple stakeholders. Thus, the community in Gampong Alue Pineung Timue is expected to experience improved welfare and optimal child development through integrated and sustainable stunting prevention efforts. The implications of this research underscore the need for synergy between government and community in tackling stunting. Through comprehensive approaches like nutritional education, access to clean water, and adequate sanitation, it is expected to significantly reduce stunting prevalence in Gampong Alue Pineung Timue. Globally, these efforts also contribute to achieving global nutrition targets aimed at reducing the number of stunted children. Keywords: Stunting Prevention; Government Policy, Nutritional Education, Community Synergy